NOTE ON A PRELIMINARY EXPERIMENT ON THE CULTURE OF SILLAGO SIHAMA (FORSKAL) AT MANGALORE - Dhulkhed, M H; Ramamurthy, S (Indian Journal of Fisheries, 2011)
The prospects of farming Sillago sihama on the edge of the South Kanamcoast have been highlighted in an earlier account (Ramamurthy and Dhulkhed,MS). As a further step, tihe culture of this fish was initiated 'On an experimentalblisis to -8:S!s'es its growth: pattern. vh!e results of thisc,study cal'ded out fmmjanuary ,to April 1974' ar:e pte,sented here